GAYA KOMUNIKASI PIMPINAN DALAM MENINGKATKAN KINERJA KARYAWAN PADA PT. WHITE AND BLUE DI PEKANBARU - Putri Wulandari; Rusmadi Azwa, (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Every chief has particular characteristic and different style of communication in managing his/her company. Those three basic system are the styles that should be used by the chief in a company. The goals of this reasearch are to know how communacation styles of the chief in advancing the performance of employess on White and Blue Company in Pekanbaru and what factors which influence the usage of communication style of the chief in advancing the performance of employess on White and Blue Company in Pekanbaru. In this research, the writer uses communication process model.This research uses qualitative methodology. Data collection technique of this research are by observation, interview, and documentation. The analysed data then will be reduced, presented and therefore will result in a general inference. The informen on this research are 10 people selected by using purposive sampling. In order to measure validity of the data, this research uses extension participation and triangulation technique.The result of this research showed that communication style used by the chief in White and Blue Company were family communication and flexible communication which led toward the equalitarian style, whereas the styles family comunication and flexible communication used by the chief on this company were carried out in free. It means that every member of organization can reveal any ideas/concepts or opinions in relax and informal situation. Thereby, the chief can give the employees such comfort situation on company and therefore the performance of the employees can be increased.Keyword : The communication style, leadership, employee performance